Data envelopment analysis for ambulance services of different service providers in urban and rural areas in Ministry of Health Malaysia - Mohd Hassan, Nor Zam Azihan; Bahari, Mohd Shahri; Aminuddin, Farhana; Mohd Nor Sham Kunusagaran, Mohd Shaiful Jefri; Zaimi, Nur Amalina; Mohd Hanafiah, Ainul Nadziha; Kamarudin, Fakarudin (Frontiers in Public Health, 2023)
Ambulance services are pivotal in any country’s health care system. An efficient ambulance service does not only decrease patient mortality rate but also allows resource prioritization for better outputs. This study aims to measure the efficiency of ambulance services provided by health facilities in the Ministry of Health (MOH), Malaysia. This cross-sectional study analyzed the efficiency of 76 Decision-Making Units (DMUs) or health facilities, consisting of 62 health clinics and 14 hospitals. Data Envelopment Analysis (DEA) was used for computing efficiency scores while adopting the Variable Return to Scale (VRS) approach. The analysis was based on input orientation. The input was the cost of ambulance services, while the output for this analysis was the distance coverage (in km), the number of patients transferred and hours of usage (in hours). Subsequent analysis was conducted to test the Overall Technical Efficiency (OTE), Pure Technical Efficiency (PTE), Scale Efficiency (SE) and Return to Scale with the type of health facilities and geographical areas using a Mann Whitney U test and Chi-Square test. The mean of OTE, PTE and SE were 0.508 (±0.207), 0.721 (±0.185) and 0.700 (±0.200) respectively. About 14.47% of the total health facilities were PTE. The results showed a significant difference in OTE and SE between ambulance services in hospitals and health clinics (p<0.05), but no significant difference in PTE between hospitals and clinics (p>0.05). There was no significant difference in efficiency scores between urban and rural health facilities in terms of ambulance services except for OTE (p<0.05). In conclusion, the ambulance services provided in healthcare facilities in the Ministry of Health Malaysia operate at 72.1 % PTE. The difference in OTE between hospitals and health clinics' ambulance services was mainly due to the operating size rather than PTE. This study will be beneficial in providing a guide to the policy makers in improving the ambulance services through readjustment of health resources and improvement in the outputs.